2006
DOI: 10.1111/j.1365-3059.2005.01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Iris yellow spot virus in onions: a new tospovirus record from India

Abstract: During 2002-03, field-infected onion ( Allium cepa ) plants, exhibiting characteristic symptoms of chlorotic spindle-or diamond-shaped lesions on the leaves and scapes with twisting or bending flower-bearing stalks, were observed in the Jalna and Nasik regions of Maharashtra, India. In the advanced stages, single spindle-shaped chlorotic lesions coalesced, leading to withering of leaves and flower-bearing stalks. The disease was transmitted to a number of virus-indicator plants by mechanical inoculation using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 3 publications
1
16
1
2
Order By: Relevance
“…The infected crop has now been removed to eradicate the infection. An earlier study confirmed the prevalence of IYSV (Tospovirus: Serogroup VI) on onion in India (Ravi et al 2006). This is the first report of the natural occurrence of GBNV (Serogroup IV of Tospovirus) infecting onion.…”
supporting
confidence: 61%
“…The infected crop has now been removed to eradicate the infection. An earlier study confirmed the prevalence of IYSV (Tospovirus: Serogroup VI) on onion in India (Ravi et al 2006). This is the first report of the natural occurrence of GBNV (Serogroup IV of Tospovirus) infecting onion.…”
supporting
confidence: 61%
“…Allexiviruses can cause significant yield reduction in garlic (14-32%) [4] and might affect onion crop in mixed infection with OYDV. A tospovirus (Irish yellow spot virus) which produces typical symptoms of diamondshaped or near-diamond shaped lesions has been previously reported in onion from western part of India [14] but the same was not observed in our experimental onion field.…”
Section: Introductioncontrasting
confidence: 50%
“…Five bulbs were grown in the glasshouse. Remaining bulbs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were stored at 4°C. Healthy plants were obtained by growing onion seeds in glasshouse under insect free conditions.…”
Section: Methodsmentioning
confidence: 99%
“…It was first observed in the USA in Idaho in 1989 (Hall et al, 1993) and then in the Netherlands in 1992, where the virus was described and characterized (Corteˆs et al, 1998). In recent years, IYSV was reported from Australia (Coutts et al, 2003), Brazil (Pozzer et al, 1999), Chile (Rosales et al, 2005), Guatemala (Nischwitz et al, this study), India (Ravi et al, 2006), Israel (Gera et al, 1998), Japan (Doi et al, 2003), La Reunion Island (France) (Robe`ne-Soustrade et al, 2006), Peru (Mullis et al, 2006), Spain (Co´rdoba-Selle´s et al, 2005) and parts of western USA (Schwartz et al, 2002;Creamer et al, 2004;Du Toit et al, 2004;Crowe and Pappu, 2005;Pappu et al, 2006a). Among the states in eastern USA, the most recent report of IYSV came from New York (Hoepting et al, 2007).…”
Section: Introductionmentioning
confidence: 60%